Penerapan Framework Bootstrap Dalam Sistem Informasi Rekam Medis Data Posyandu dengan Metode Waterfall - Yunus Anis; Purwatiningtyas Purwatiningtyas; Retnowati Retnowati; Elsa Awalin Nur Fajrina (Universitas Budi Darma, 2022)
Bootstrap is a combined framework of CSS and JavaScript that is offered as an alternative among other frameworks with the intention of providing consistency to the interface development stage in building a website, one of which is the website at the Posyandu Kemuning Gajah Village. The problems that arise are related to recording visitor data manually in the register book, which is often done because there are so many things that must be recorded such as weight, developmental data for mothers, children under five, maternal development data, other personality data related to pregnant women and toddlers visiting posyandu. . For this reason, it is necessary to support an information system for recording participant activities so that the number of participants does not need to be developed in data processing and re-accessing so that data redundancy does not arise. The system that will be created using the bootstrap framework includes the participant registration process and data processing for posyandu participants, so that they are able to manage data and generate data reports in a valid and correct manner. Testing with the blackbox method shows that the entire system built from the implementation of the login form to the print report shows that everything has been successfully implemented in the system.